Phosphorus as a promoter of a nickel catalyst to obtain 1-phenylethanol from chemoselective hydrogenation of acetophenone - Costa, Dolly Carolina (2019)
Two catalysts were prepared using monodisperse pre-synthetized nanoparticles of metallic nickel and nickel phosphides with the same average diameter. Both nanoparticles species were deposited on the same support: mesoporous silica nano-spheres of MCM-41. This support is suitable to inhibit agglomeration and sintering processes during preparation steps. Therefore, two supported and activated catalysts with the same average nanoparticles diameter were obtained. They differ only in the nature of the active species: metallic nickel and nickel phosphides. The effect of the presence of a second element (phosphorus), more electronegative than nickel, on the activity and selectivity in the chemoselective hydrogenation of acetophenone was studied. The reaction conditions were: H2 pressure of 1 MPa, 80°C using n-heptane as solvent. With the aim to understand the catalytic results, nanoparticles, support and catalysts were carefully characterized by X-ray diffraction, diffuse light scattering, transmission electron microcopy, high resolution transmission electron microcopy, selected area electron diffraction, scanning electron microcopy, Fourier transformer infrared spectroscopy, N2 adsorption at -196 °C, atomic absorption, H2 and CO chemisorption and volumetric oxidation. Considering these results and geometric and electronic characteristics of the surface of both active species, a change in the adsorption intermediate state of acetophenone in presence of phosphorus is proposed to explain the hydrogenation chemoselectivity of nickel phospides